Cover Image. (21st February 2019) - Unknown
Abstract : 1. Caption: Larvae of California Grunion (Leuresthes tenuis) at 20 days post hatching, Credit: D. Johnson. 2. Caption: Male hihi, Credit: Eric Wilson. 3. Caption: N/A, Credit: Martin Mallet. 4. Caption: Mosquitoes are maintained in crowded, artificial environments in the laboratory, Credit: Perran Ross. 5. Caption: Mouse lemur caught in Mandena, Credit: Refaly Ernest. 6. Caption: Wildcat, Credit: Pete Cairns